UOʻK 622.274.4 KOVULDI OLTIN KONI UCHUN TEZ QOTUVCHI MONOLIT TO‘LG‘AZMA MATERIALLARNI TAYYORLASH METODIKASI - Mislibayev, I.T.; Alimov, Sh.M. (SCIENCE and SOCIETY, 2024)
The article discusses the development system used at the Kovuldi gold mine, owned by the Almalyk Mining and Metallurgical Combine joint-stock company, i.e. backfilling of mined-out space using a methodology for selecting the composition of backfill materials during backfill mining operations and the possibility of technical application were considered.
Keywords: monolithic backfill; red sand; fraction sizes; transportability (delivery to the chamber); chamber; development system; cement; marble sand